تدبر سورة الفاتحة من خلال توجيه ما فيها من قراءات : Contemplating the Meaning of al-Fatihah Through the Variant Readings of the Qurʾān - Shalash, Adnan Moh’d Abdullah Shalash; Fawaz Farhan Al Doumani (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
This study deals with the variant readings of Surat Al-Fatihah transmitted in two influential works of qiraat, namely al-Ibanah ‘an Ma’ani al-Qiraat by Imam Makki bin Abi Talib Al-Qaisi, and al-Nashr fi al-Qira’at al-‘Ashr by Imam Ibn al-Jazari along with several other books. The research aims to collect frequent and abnormal recitations related to Surat Al-Fatihah based on guidance from specific authors and review whether the various recitations affect the meaning of the Surah; as the meaning is complementary, not contradictory or not contradictory. Since many of the variant readings in the linguistic works and exegesis of the Quran were not attributed to any scholars, this paper will note these unattainable discussions. The importance of the research lies in some guidance in contemplating Surah Al-Fatihah. In this study, the researchers used the inductive method in collecting the recitations from its sources, then the descriptive-analytical way. Among the most important results of the study is Surat Al-Fatihah - with its various recitations - is full of meanings that should be followed and studied in deepening its contemplation.